Improving Urban Mobility for the Visually Impaired using the Awareness Quality - Moura, Ana Maria da Mota; de Oliveira, Romeu Ferreira; Fernandes, Eduardo; Caetano, Lauro de Lacerda; Manoel, Luciene; Leite, Julio Cesar Sampaio do Prado (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Urban mobility for disabled people is a hard challenge. The technology of the Internet of Things (IoT) might empower these individuals by contributing to their safety and security. In the case of the visually impaired, smart canes are critical components for tackling the challenge of mobility for this population. These types of devices, when integrated into the IoT ecology, may augment their effectiveness. However, this integration is tricky, and we should plan it accordingly. We show how the use of quality requirements (NonFunctional Requirements) can contribute to the development of these types of systems. In this context, self-adaptive systems may improve the solution. To properly accomplish the expected benefits from self-adaptation, we demonstrate how the reuse of an awareness catalog contributes to the derivation of modular software architecture. Our demonstration focus on a real self-adaptive system, which was re-engineered to connect better the different parts of an IoT solution that supports urban mobility for the visually impaired.